2023
DOI: 10.20473/ijph.v18i1.2023.72-81
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Compliance With Iron Tablet Consumption and Iron Nutrition Intake With Pregnant Women's Hemoglobine Consumption

Abstract: Introduction: During pregnancy, the need for iron increases, which triggers anemia. Anemia can be described as a decline in the hemoglobin level below a critical level. Meanwhile, based on a preliminary study, 10 out of 13 pregnant women were not obedient in taking iron tablets (76, 92%). The prevalence of anemia at Tanah Kalikedinding Community Health Center in 2015 remained high. Method: The analytical study used a cross-sectional design. The group of pregnant women in the third trimester who received Fe tab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…14 The results from the statistical tests between iron intake and hemoglobin levels indicated a significant correlation. It aligns with research conducted by Ambarsari et al (2023), demonstrating that there is a correlation between iron intake and hemoglobin levels of pregnant women. It revealed that pregnant women with sufficient iron intake tend to have normal hemoglobin levels, while those with insufficient iron intake tend to have abnormal hemoglobin levels.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…14 The results from the statistical tests between iron intake and hemoglobin levels indicated a significant correlation. It aligns with research conducted by Ambarsari et al (2023), demonstrating that there is a correlation between iron intake and hemoglobin levels of pregnant women. It revealed that pregnant women with sufficient iron intake tend to have normal hemoglobin levels, while those with insufficient iron intake tend to have abnormal hemoglobin levels.…”
Section: Discussionsupporting
confidence: 87%
“…It revealed that pregnant women with sufficient iron intake tend to have normal hemoglobin levels, while those with insufficient iron intake tend to have abnormal hemoglobin levels. 15 As mentioned before, most of the pregnant women with normal hemoglobin levels have sufficient iron intake, where they have consumed iron tablet supplements and food that contains much iron (such as chicken, fish, and beef). 16 The iron intake of respondents in this research is compared to the Adequacy of Nutritional Rate (RDA) based on the age of the mother and their gestational age.…”
Section: Discussionmentioning
confidence: 99%